Antimicrobial skin peptides in premature infants: Comparison with term infants and impact of perinatal factors - Humberg, Alexander; Neuenburg, Lisa; Boeckel, Hannah; Fortmann, Mats Ingmar; Härtel, Christoph; Herting, Egbert; Hinrichs, Heilwig; Rademacher, Franziska; Harder, Jürgen (Frontiers in Immunology, 2023)
Introduction: Preterm infants have an immature epidermis barrier function which may lead to an increased permeability to pathogens. On the surface of the human skin, antimicrobial peptides (AMPs) are important molecules of the innate immune system, have broad antimicrobial properties and provide an essential role in integrity of the microbiome. Given the marked susceptibility of preterm infants to infection, we hypothesize a decreased expression of AMPs on the skin of preterm infants. Materials and Methods: In a prospective single-center study with 35 preterm and 20 term infants we analyzed skin rinsing probes for the presence of the AMPs psoriasin (S100A7) and ribonuclease 7 (RNase 7) via enzyme-linked immunosorbent assay. Samples were taken from preterm infants < 34 0/7 weeks gestational age (mean±SD gestational age 28.8±2.4 weeks) on day 0, 7, 14 and 28 after birth. Term infants (> 36 6/7 weeks) (controls) were washed on day 0 and on day 28. Results: Psoriasin and RNase 7 were both expressed on skin of preterm and term infants and increased in concentration significantly over time. RNase 7 was more expressed in term infants on day 0 (preterm 1.1 [0.7-2.9] vs. term 2.0 [1.1-3.4] ng/ml, p = 0.017). On day 28, premature infants showed higher values of psoriasin (preterm 10.9 [5.6-14.2] vs. term 6.3 [3.4-9.0] ng/ml, p < 0.001). Notably, preterm infants with infectious or inflammatory context driven by histological proof of chorioamnionitis, early-onset sepsis or late-onset had higher concentrations of psoriasin as compared to non-affected preterm infants. After exclusion of infants with inflammatory hit, median concentrations of RNase 7 and psoriasin did not differ between preterm and full-term infants on day 0 and day 28. Discussion: Psoriasin and RNase 7 concentrations increase over time on the skin of newborn infants and seem to play a role in the first defense against infection. This is of particularly interest as the role of AMPs on a maturing skin microbiome and its possible new prevention strategies is unclear and needs to be determined.